Urban Regeneration for the Resilient City: Implementation of Sustainable Urban Drainage Solutions in Pisa's High Flash Flood Risk Areas - Luisa Santini; Greta Frosini; Cinelli Fabrizio (Environmental Science and Sustainable Development)
Policies and international cooperation widely acknowledge the imperative to enhance the resilience of cities, ensuring effective multi-risk disaster management. Nature-based solutions (NBS) provide approaches aimed at conserving, sustainably managing, and preserving natural ecosystems. This research, funded by UNIPI PRA_2022_22, titled “Mitigating Risks in Urban Areas”, aims to develop a methodology to analyse and evaluate the benefits of increased resilience in urban contexts following the implementation of NBS. To control water runoff sources, improve soil infiltration, retain, or detain water volume, and filter contaminants, we designed small-scale sustainable urban drainage interventions in 4 areas of the city of Pisa prone to high hydraulic and flash flood risk. To verify their impact on stormwater management, the i-tree Hydro Plus was used. We tested the software using input data that simulated generic interventions, such as green roofs, permeable pavements, and rain gardens. The application showed promising results, but several challenges were encountered in data acquisition, as much of the data was not readily available, requiring the use of default values in some cases. Additionally, the complexity of the i-Tree Hydro Plus software limited its practical application to those with specialized expertise and, in its current state, unfortunately, it is not an accessible tool for local authorities.